Research Progress of Curcumin Intervening the Mycotoxin-induced Toxicity - Honglin LI; Yifang LI; Chi ZHANG; Hongyuan ZHOU; Ting GUO; Yuhao ZHANG; Liang MA (Shipin gongye ke-ji, 2022)
To intervene and control the toxic effects of the hazard factors using nature products is one of the research hotspots recently in the field of food safety. Curcumin, as a hydrophobic polyphenolic compound extracted from the traditional spice turmeric, has strong anti-inflammatory, anti-oxidation, anti-cancer, enhancing immunity and other activities. Recent studies have shown that curcumin can intervene some toxicities induced by mycotoxins such as Aflatoxin B1, Ochratoxin A, Zearalenone, Fumonisin B1 and Deoxynivalenol, thereby reducing damages and enhancing resistance in body. In this paper, the toxicities of main mycotoxins were briefly summarized at first. And then, the intervention effects and its related mechanism of curcumin on the mycotoxin-induced toxicities in the latest five years were emphatically elaborated, mainly from the aspects of reducing ROS production and lipid peroxidation, regulating related pathways and improving intestinal flora. Finally, the potential problems that to be urgently solved are discussed. Our review aimed at providing the theoretical bases for the in-depth development and utilization of curcumin in the health industry as well as to broaden the ideas for the research and development of other plant-derived functional components.